Perbandingan Flavonoid Total dan Aktivitas Antioksidan Fraksi Etil Asetat Biji Kelor (Moringa oleifera L.) dan Biji Kecipir (Psophocarpus tetragonolobus L.) - Annisa Krisridwany; Miftah Rizkia Tatra; Dyani Primasari Sukamdi (Jurnal Farmasi Indonesia, 2022)
Moringa seeds (Moringa oleifera L.) and winged bean seeds (Psophocarpus tetragonolobus L.) are medicinal plants used by the community as food and as traditional medicine preparations. They also contain compounds that have potential as antioxidants. It is necessary to compare the levels of one of the compounds and test the antioxidant activity. This study aims to determine the comparison of total flavonoid levels and antioxidant activity in the ethyl acetate fraction of Moringa oleifera L. and winged bean seeds (Psophocarpus tetragonolobus L). The ethanol extracts were partitioned by using n-hexane, ethanol, and ethyl acetate. This research focused on the ethyl acetate fraction. The total flavonoid determination was based on measuring each fraction's absorbance value at a wavelength of 446 nm and using a quercetin comparator. The antioxidant activity test of ethyl acetate fraction of Moringa oleifera L. and winged bean seeds (Psophocarpus tetragonolobus L.) was carried out by measuring the reduction of each fraction against DPPH radicals (1,1- diphenyl 2-picrilhidrazil) using UV-Vis spectrophotometry method at a wavelength of 517 nm. The antioxidant activity test was carried out by using a comparison of vitamin C. The results showed the total flavonoid level of ethyl acetate fraction of Moringa oleifera L seeds and winged bean seeds (Psophocarpus tetragonolobus L.) were 42.80 ± 1.61 mg QE/g and 71.56 ± 5.50 mg QE/g, respectively while the antioxidant activities of ethyl acetate fraction of Moringa oleifera L seeds and winged bean seeds (Psophocarpus tetragonolobus L.) were 134.34 ppm and 179.57 ppm, respectively. The result showed that the ethyl acetate fraction of Moringa seeds (Moringa oleifera L.) had moderate antioxidant activity and more potent compare to Winged bean seeds; however, Winged bean seeds's flavonoid total was higher than Moringa seeds’s. Keyword : Antioxidant; DPPH; Flavonoid; Moringa oleifera L., Psophocarpus tetragonolobus L., seed